Author 
Message 
TAGS:

Hide Tags

Senior Manager
Joined: 26 Jul 2005
Posts: 313
Location: Los Angeles

Is x/m(m^2 + n^2 + k^2) = xm + yn + zk? (1) z/k = x/m (2) [#permalink]
Show Tags
27 Oct 2005, 16:35
Question Stats:
0% (00:00) correct
0% (00:00) wrong based on 3 sessions
HideShow timer Statistics
Is x/m(m^2 + n^2 + k^2) = xm + yn + zk?
(1) z/k = x/m
(2) x/m = y/n



Manager
Joined: 20 Mar 2005
Posts: 201
Location: Colombia, South America

I think is C
x/m(m^2 + n^2 + z^2) = xm + yn + zk
that is equal to
xm + xn^2/m + xz^2/n = xm + yn + zk
from I: x/m = y/n then xn = ym and from there (xn*n)/m is equal to
ym*n/m equal to yn
so insuff
from ii, do the same stuff as i and you get zk
so insuff
taking both it works so C



Senior Manager
Joined: 26 Jul 2005
Posts: 313
Location: Los Angeles

Right again  OA is C.



Intern
Joined: 14 Sep 2010
Posts: 22

Re: Is x/m(m^2 + n^2 + k^2) = xm + yn + zk? (1) z/k = x/m (2) [#permalink]
Show Tags
18 Nov 2011, 03:39
Is x/m(m^2 + n^2+ k^2) = xm + yn + zk?
xm^2 + xn^2 + xk^2 = xmm +ynm +zkm?
Is xn^2 + xk^2 = ynm + zkm?
(1) z/k = x/m (xk = mz)
xk^2 = (xk)k = (mzk)
xn^2 + xk^2 = ynm + zkm =
xn^2 = ynm? xn = my?
(2) x/m = y/n (xn = my)
xn^2 = (xn)n = (my)n
xn^2 + xk^2 = ynm + zkm =
xk^2 = zkm? xk = mz?
Put (1) and (2) together
xn^2 + xk^2 = ynm + zkm =
(my)n + (mz)k = ynm + zkm
Both statements used = Answer C
Posted from my mobile device



Senior Manager
Joined: 13 May 2011
Posts: 307
WE 1: IT 1 Yr
WE 2: Supply Chain 5 Yrs

Re: Is x/m(m^2 + n^2 + k^2) = xm + yn + zk? (1) z/k = x/m (2) [#permalink]
Show Tags
18 Nov 2011, 05:19
is xm^2+xn^2+xk^2=xm^2+ynm+zkm i. e. xn^2+xk^2=ynm+zkm statement 1: xk=zm xn^2=ynm Not Sufficient Statement 2: ym=xn xk^2=zkm Not Sufficient Together: xn^2+xk^2=xn^2+xk^2 Sufficient




Re: Is x/m(m^2 + n^2 + k^2) = xm + yn + zk? (1) z/k = x/m (2)
[#permalink]
18 Nov 2011, 05:19







